Javanese Philosophy-Based Islamic Religious Education: Synergy of Tepa Selira and Cablaka Values in Developing Students’ Mental Health - Nur Rahmah Al Haqq; Amirul Salam; Kholil Lur Rochman; Norma Fitria (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
This article explores the synergy between Islamic religious education and Javanese philosophy, specifically the values of tepa selira (empathy and tolerance) and cablaka (honesty and openness), as a strategy to foster the mental health of Generation Z students. Amid the rapid wave of digitalization and social pressures affecting today’s youth, mental health has become a critical issue that can no longer be overlooked. Generation Z, living in an instant and highly competitive environment, is vulnerable to stress, anxiety, and identity crises. Therefore, an educational approach is needed one that not only emphasizes cognitive religious aspects but also considers emotional and social balance. This study uses a qualitative approach through a literature review and critical analysis of sources related to Islamic education, educational psychology, and Javanese culture. The findings show that tepa selira cultivates students’ empathy, social awareness, and emotional regulation skills. Meanwhile, cablaka encourages the courage to express oneself honestly and supports psychological well-being. These two values align with Islamic teachings on noble character and inner balance, making them highly relevant for integration into the Islamic Religious Education curriculum. This integration allows students to develop mental health not only through spiritual rituals but also through cultural values. Javanese-philosophy-based Islamic religious education has the potential to become a contextual, humanistic educational model that addresses the essential aspects of youth development in the digital era.